Net effects of pasture-raised poultry on arthropod communities driven by top-down and bottom-up forces in a mixed-cover crop system - Garcia, Karina; Halmos, Viktor; Thongjued, Kantima; Dupuis, Julian R.; Gonthier, David J. (Frontiers in Sustainable Food Systems, 2023)
As consumer demand and grower interest for pasture-raised poultry grow, more research is needed to understand the ecological consequences of the integration of pasture-raised poultry on agroecosystems. Poultry could have profound and complex net effects on arthropod communities given their high density per area, broad omnivory, and high manure deposition. Further, some studies suggest poultry may aid in the suppression of agricultural pests in integrated systems. Yet, unlike wild birds, pasture-raised poultry have received little attention in the field of agroecological net effects. Across 2 years, we examined how an absence (control- cover crop only), low- [9.51 m2 (102.4 ft.2) of pasture per broiler] and high-densities [4.76 m2 (51.2 ft.2) of pasture per broiler] of broilers impacted cover crop biomass, ground-dwelling arthropods, and plant-dwelling arthropods in a rotationally grazed mixed-cover crop system. High- and low-density poultry treatments had 7.8-fold and 3.5-fold less cover crop biomass compared to the control treatment after 1–3 days of access, respectively. Despite the depletion of cover crops, there were substantial positive effects on ground-dwelling arthropods. Most striking was the impact on house fly larvae where high-density poultry treatments had 1,432-fold more house fly larvae relative to the control treatments. Dung beetle, spider, and rove beetle mean relative abundances increased 47-, 2.4-, and 3.5-fold, respectively, from the control treatment to the high-density poultry treatment. In contrast, the mean relative abundances of plant-dwelling arthropod orders Coleoptera, Hemiptera, and Hymenoptera were 4-, 5-, and 3.6-fold higher, respectively, in the control treatment relative to the high-density poultry treatment. Overall, these results suggest that pasture-raised poultry may promote the abundance of ground-dwelling arthropods through bottom-up mechanisms by depositing fecal material. However, poultry decreased the abundance of plant-dwelling arthropods, likely by destroying their habitat and food resources (via consumption and trampling of cover crop) and direct consumption of arthropods. While the integration of poultry into crop rotations is thought to benefit crop yield through nutrient deposition in the form of manure, this study suggests it may also stimulate the soil and ground-foraging arthropod food webs. This study is the first to evaluate the impacts of pastured poultry to arthropod communities in a mixed-cover crop system.